2003
DOI: 10.1021/ac0341618
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Biomarkers in Rat Urine Using LC/Electrospray Ionization-MS and Two-Way Data Analysis

Abstract: Biofluids, like urine, form very complex matrixes containing a large number of potential biomarkers, that is, changes of endogenous metabolites in response to xenobiotic exposure. This paper describes a fast and sensitive method of screening biomarkers in rat urine. Biomarkers for phospholipidosis, induced by an antidepressant drug, were studied. Urine samples from rats exposed to citalopram were analyzed using solid-phase extraction (SPE) and liquid chromatography mass spectrometry (LC/MS) analysis detecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
118
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(119 citation statements)
references
References 24 publications
0
118
0
1
Order By: Relevance
“…Cholestasis-induced bile duct cell necrosis and subsequent membrane breakdown caused by ANIT and as the result of the serum examinations may account for the elevation of urinary bile acids at 7-55 hours. PAG has been reported to be a potential biomarker for phospholipidosis (Dieterle et al 2006;Espina et al 2001;Idborg-Bjorkman et al 2003;Nicholls et al 2000), and alteration of PAG levels has been found in urinary metabolic fingerprinting for ANIT-induced intrahepatic cholestasis using LC-MS (La et al 2005). PAG is the end product of phenylalanine metabolism in rodents (James et al 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Cholestasis-induced bile duct cell necrosis and subsequent membrane breakdown caused by ANIT and as the result of the serum examinations may account for the elevation of urinary bile acids at 7-55 hours. PAG has been reported to be a potential biomarker for phospholipidosis (Dieterle et al 2006;Espina et al 2001;Idborg-Bjorkman et al 2003;Nicholls et al 2000), and alteration of PAG levels has been found in urinary metabolic fingerprinting for ANIT-induced intrahepatic cholestasis using LC-MS (La et al 2005). PAG is the end product of phenylalanine metabolism in rodents (James et al 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Major efforts have been made to improve the feature extraction, quantification, and identification. A number of algorithms and software have been developed that greatly facilitate the data processing of LC/MS data [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] . As this is not the focus of the review, we will skip the details.…”
Section: Bottom-up and Top-down Metabolomicsmentioning
confidence: 99%
“…33 for an overview of Chemometrics analysis techniques) to extract the major spectral components in LC-MS profiling of urine (34,35), a notably simpler mixture than tissue or serum. In this manner, a data matrix, X, defining a single LC-MS experiment, with rows corresponding to time points and columns to m/z values, was resolved into a set of "pure" spectral profiles.…”
Section: Mid-level Processing-peak Detection and Quantificationmentioning
confidence: 99%